The Efficacy of Doxylamine Succinate and Pyridoxine Combination in Nausea and Vomiting Of Pregnancy - Hina Shams Solangi; Rubina Hussain; Shahina Ishtiaque (ziauddin University, 2024)
Background: Nausea vomiting of pregnancy (NVP) is a common problem .A severe form called hyperemesis gravidarum occurs in 0.3-2.3% of pregnancies, which can adversely affect the lifestyle. This study is conducted to improve the confidence of obstetricians for treatment of nausea and vomiting of pregnancy. Objective: To determine the efficacy of doxylamine succinate with pyridoxine combination in nausea & vomiting of early pregnancy. Methods: Study conducted at Dr. Ziauddin University and Hospitals Karachi, from 25-02-2011 to 25-07-2011. Study design was case series, during the period of study total number of OPD patients in gynaecology and obstetrics department Ziauddin hospital were 821, out of them 190 patients of 20 years to 39 years of age with 9+ 2 weeks gestation were enrolled and sample was taken by Consecutive sampling. Results: 182 (95.8%) patients reported improvement in symptoms i.e. positive efficacy, 7 patients ( 3.7%) reported no difference in nausea vomiting & only 1 patient i.e. 0.5% reported aggravation of her symptoms. Total PAQUE score before treatment was as high as 12.3526 with standard deviation of 2.12739, which reduced to 5.7211 with standard deviation 2.0908 after treatment of nausea vomiting with doxylamin succinate + pyridoxine combination. P value calculated for total PAQUE score before and after treatment is 0.000 Conclusion: This study concluded that for nausea and vomiting of pregnancy, doxylamine succinate is effective when given for moderate to severe symptoms. So it should be considered as 1st line of treatment for nausea and vomiting of pregnancy. KEY WORDS: Doxylamine succinate and pyridoxine combination, nausea vomiting of pregnancy, efficacy.